Na pograniczu psychologii i pedagogiki – czyli życie i działalność Ludwiki Karpińskiej-Woyczyńskiej - Groth, Jarosław; Waszyńska, Katarzyna (Wydawnictwo Naukowe UAM, 2014)
The purpose of this paper is to present the achievements and the person of Dr. Louise Karpińska- Woyczyńska, an outstanding researcher and academic lecturer who implemented in practice scientific developments and popularized psychological and pedagogical knowledge in the first decades of the twentieth century. Karpińska-Woyczyńska belongs to the group of Polish scientists hardly remembered today. This article aims to preserve the memory of the pioneers of Polish science. The opportunity to see the humanistic ethos of Karpińska-Woyczyńska also seems to be important in shaping the identity of those who study, conduct research and use the discoveries of science in practice today. The extant archival material, allowing only a rudimentary recreation of her accomplishments, shows the uniqueness of this social activist and science enthusiast, who disseminated knowledge from the fields of psychology, pedagogy and psychoanalysis.
On the Border of Psychology and Pedagogy – the Life and Work of Louise Karpińska-Woyczyńska
Keywords: history of psychology; history of educational thought; psychotechnics; counseling